Rhesus macaques show increased resistance to repeated SHIV intrarectal exposure following a heterologous regimen of rVSV vector vaccine expressing HIV antigen - Joseph Jelinski; Monika M. Kowatsch; Marc-Alexandre Lafrance; Alice Berger; Jannie Pedersen; Hiva Azizi; Yue Li; Florine Scholte; Alejandro Gomez; Natasha Hollett; Toby Le; Matthew Wade; et al. (Emerging Microbes and Infections)
Despite the human immunodeficiency virus (HIV) pandemic continuing worldwide for 40 years, no vaccine to combat the disease has been licenced for use in at risk populations. Here, we describe a novel recombinant vesicular stomatitis virus (rVSV) vector vaccine expressing modified HIV envelope glycoproteins and Ebola virus glycoprotein. Three heterologous immunizations successfully prevented infection by a different clade SHIV in 60% of non-human primates (NHPs). No trend was observed between resistance and antibody interactions. Resistance to infection was associated with high proportions of central memory T-cell CD69 and CD154 marker upregulation, increased IL-2 production, and a reduced IFN-γ response, offering insight into correlates of protection.